Building on our achievements to transform the WEFE nexus - McCartney, Matthew P.; Ringler, Claudia (CGIAR, 2024)
We have recently launched the NEXUS Gains 2023 annual technical report which shows how the Initiative has built on previous achievements to contribute to a positive transformation of the water–energy–food–ecosystems (WEFE) nexus. By facilitating knowledge generation and exchange, innovative solutions, and strategic partnerships, the CGIAR Initiative on NEXUS Gains is promoting systems thinking and enhancing efforts to achieve inclusive development whilst simultaneously conserving biodiversity and mitigating climate change impacts.